Particulate matter as a real danger for health for Zaporizhzhia citizens - Волкова, Юлія Володимирівна; Volkova, Yu. V. (Запорізький державний медичний університет, 2017)
Relevance. Air pollution represents the biggest environmental risk to health. In 2012, one out of every nine deaths was the result of air pollution-related conditions. Of those deaths, around 3 million are attributable solely to ambient (outdoor) air pollution [WHO, 2016]. Particulate matter (PM) affects more people than any other pollutant. Their fine fractions are the most destructive for health – 10 micron or less diameter (≤PM10). The danger of these substances is determined, forward because of the fact that they consist of the difficult mixture of solid and liquid particles of organic and inorganic substances, which are present in the increased level in the air, and because of ability to penetrate deeply to lungs and sag there.